Refleksi Guru Dalam Mengajar Bahasa Inggris Pada Masa Sebelum Pandemi Dan Saat Pandemi - Fernanda, Andri; Ferianda, Sandy; Fitri. K, Dian (Asosiasi Ide Bahasa Kepri, 2023)
This research aims to reveal teachers' reflections in teaching English during the pre-pandemic period and during the pandemic. Before the pandemic, a teacher's English instruction might have focused more on direct interaction in the classroom, with an emphasis on oral communication and group activities. Teachers can easily provide real-time feedback to students, facilitate live discussions, and provide open-ended materials directly. However, during the pandemic, English language teaching has faced new challenges by maintaining distance learning. By using the theoretical concept of Baker (1996) regarding Self-Reflection combined with Kentnor (2015) regarding the Online Learning System, it becomes the right composition for implementing learning during the Covid-19 Pandemic. This study uses a qualitative method. The results of this research reveal about (1) Teacher Reflections in Teaching English in the Pre-Pandemic Period (2) Teacher Reflections in Teaching English During the Pandemic. This research is important as a reflection that can be used by teachers and lecturers in the teaching and learning process before and during the pandemic.